ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI TAX AVOIDANCE DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Khusnul, Riska; Bawono, Andy (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to investigate the effects of profitability, leverage, sales growth on the likelihood of Tax Avoidance, incorporating firm size as a moderating factor, The analysis focuses on companies within the Consumer Non-Cyclical segment recorded on the Indonesia Stock Exchange for the period of 2020-2022. The data were subjected to classical assumption testing and analyzed with the assistance of SPSS form 26. The results reveal that, profitability and sales growth are recognized as two variables that impact Tax Avoidance. In any case, the directing variable, firm size, does not appear a noteworthy part in fortifying or debilitating the relationship between profitability, leverage, and sales growth with Tax Avoidance.